Optimization and scale up of production of the PSMA imaging agent [18F]AlF-P16-093 on a custom automated radiosynthesis platform - David Alexoff; Seok Rye Choi; Karl Ploessl; Dohyun Kim; Ruiyue Zhao; Lin Zhu; Hank Kung (SpringerOpen, 2024)
Abstract Background Recent advancements in positron emission tomograph (PET) using prostate specific membrane antigen (PSMA)-targeted radiopharmaceuticals have changed the standard of care for prostate cancer patients by providing more accurate information during staging of primary and recurrent disease. [68Ga]Ga-P16-093 is a new PSMA-PET radiopharmaceutical that demonstrated superior imaging performance in recent head-to-head studies with [68Ga]Ga-PSMA-11. To improve the availability of this new PSMA PET imaging agent, [18F]AlF-P16-093 was developed. The 18F-analog [18F]AlF-P16-093 has been synthesized manually at low activity levels using [18F]AlF2+ and validated in pre-clinical models. This work reports the optimization of the production of > 15 GBq of [18F]AlF-P16-093 using a custom automated synthesis platform. Results The sensitivity of the radiochemical yield of [18F]AlF-P16-093 to reaction parameters of time, temperature and reagent amounts was investigated using a custom automated system. The automated system is a low-cost, cassette-based system designed for 1-pot syntheses with flow-controlled solid phase extraction (SPE) workup and is based on the Raspberry Pi Zero 2 microcomputer/Python3 ecosystem. The optimized none-decay-corrected yield was 52 ± 4% (N = 3; 17.5 ± 2.2 GBq) with a molar activity of 109 ± 14 GBq/µmole and a radiochemical purity of 98.6 ± 0.6%. Run time was 30 min. A two-step sequence was used: SPE-purified [18F]F− was reacted with 80 nmoles of freeze-dried AlCl3·6H2O at 65 °C for 5 min followed by reaction with 160 nmoles of P16-093 ligand at 40 °C for 4 min in a 1:1 mixture of ethanol:0.5 M pH 4.5 NaOAc buffer. The mixture was purified by SPE (> 97% recovery). The final product formulation (5 mM pH 7 phosphate buffer with saline) exhibited a rate of decline in radiochemical purity of ~ 1.4%/h which was slowed to ~ 0.4%/h when stored at 4 °C. Conclusion The optimized method using a custom automated system enabled the efficient (> 50% none-decay-corrected yield) production of [18F]AlF-P16-093 with high radiochemical purity (> 95%). The method and automation system are simple and robust, facilitating further clinical studies with [18F]AlF-P16-093.